Retinopathy of prematurity at CNHU-HKM in Cotonou, BENIN - Bagnan Tossa, Léhila; ABOUKI, CHAKIRATOU O.A.; TCHIAKPÈ-ENIANLOKO, Nicole (My University, 2024)
Introduction : Retinopathy of prematurity is one of the leading causes of preventable visual impairment in children. It was first described by Terry in 1942 under the generic terms of retrolental fibroplasia. Objective : To determine the epidemiological and clinical profile of retinopathy in preterme newborns in the neonatology unit of CNHU-HKM Patients and methods : This is a prospective study with descriptive and analytical aims , conducted from August 1, 2019 to January 9,2020. All prematur newborns admitted to the neonatology unit of CNHU-HKM in Cotonou during the study period were included. The data were analyzed using Epi info sofware. Proportion were compared using the chisquare statistical test and a value of p< 0,05 was considered significant. Authorizatin from the head od department and the genera director of the hospital was obtained. Results : The frequency of retinopathy was 20,6%. The majority of retinal lesions observed were at stage 1 (68,4%) represented by a line of demarcation. All lesions were located in zone 3. Low gestational age (p=0,042), blood transfusion (p=0,019) and maternal fetal infection (p=0,017) were the factors associated with retinopathy of prematurity. Conclusion : it appareas necessary to set up a systematic screening program in all neonatology units to better assess the extent of this pathology.
Keywords: retinopathy of prematurity; visual impairment; associated factors; systematic screening